![x = - b + - \sqrt{b {}^{2} } - 4ac \div 2a x = - b + - \sqrt{b {}^{2} } - 4ac \div 2a](https://tex.z-dn.net/?f=x+%3D++-+b+%2B++-++%5Csqrt%7Bb+%7B%7D%5E%7B2%7D+%7D++-+4ac++%5Cdiv+2a)
Attachments:
![](https://hi-static.z-dn.net/files/d96/9229cbd2af91d6aefc8b2f5ded5e24fe.jpg)
Answers
Answered by
0
The roots of the equation are
and
.
Step-by-step explanation:
The expression is:
The following equation is a quadratic equation.
The roots of a quadratic equation is given by:
Here,
a = 15
b = -1
c = -28
Compute the roots of the equation as follows:
Thus, the roots of the equation are and
.
Similar questions